Fabrication and corrosion resistance of Mg-Zn-Y-based nano-quasicrystals alloys - Zhifeng Wang; Weimin Zhao; Chunling Qin; Yan Cui (Materials Research, 2012)
A wedge-shaped copper mold was used to fabricate micro quasicrystals(QCs). Stable Mg-Zn-Y-based nano-QCs were directly synthesized through this simple route instead of crystallization from metallic glasses or complicated forming processes at high temperature. The study showed that on the tips of the wedge-shaped ingots, the minimum diameter of nano-QCs approach to 4~6 nm. The main size of nano-QCs is about 10~30 nm. The maximum microhardness of QCs has been dramatically improved to about HV440 which increased by about 280% compared with that of the petal-like QCs fabricated under common cast iron mold cooling conditions. Possessing a certain negative enthalpy of mixing and existence of Frank-Kasper-type phases determined the formation of Mg-Zn-Y-based nano-QCs. The further electrochemical studies showed that Mg71Zn26Y2Cu1 nano-QC alloy possess high corrosion resistance in simulated seawater and its corrosion resistance is much better than those of the Mg72Zn26Y2 and Mg71Zn26Y2Cu0.5 Ni0.5 nano-QC alloys.